Exercise Experiences and Changes in Affective Attitude: Direct and Indirect Effects of In Situ Measurements of Experiences - Sudeck, Gorden; Schmid, Julia; Conzelmann, Achim (Frontiers in Psychology, 2016)
Objectives. The purpose of this study was to examine the relationship between exercise experiences (perceptions of competence, perceived exertion, acute affective responses to exercise) and affective attitudes toward exercise. This relationship was analyzed in a non-laboratory setting during a 13-week exercise program. Materials and methods. 56 women and 49 men (aged 35-65 years; Mage = 50.0 years; SD = 8.2 years) took part in the longitudinal study. Affective responses to exercise (affective valence, positive activation, calmness) as well as perceptions of competence and perceived exertion were measured at the beginning, during, and end of three exercise sessions within the 13-week exercise program. Affective attitude toward exercise were measured before and at the end of the exercise program. A two-level path analysis was conducted. The direct and indirect effects of exercise experiences on changes in affective attitude were analyzed on the between-person level: Firstly, it was tested whether perceptions of competence and perceived exertion directly relate to changes in affective attitude. Secondly, it was assessed whether perceptions of competence and perceived exertion indirectly relate to changes in affective attitudes—imparted via the affective response during exercise. Results and conclusion. At the between-person level, a direct effect on changes in affective attitude was found for perceptions of competence (β = .24, p < .05). The model revealed one significant indirect pathway between perceived exertion and changes in affective attitude via positive activation: On average, the less strenuous people perceive physical exercise to be, the more awake they will feel during exercise (β = -.57, p < .05). Those people with higher average levels of positive activation during exercise exhibit more improvements in affective attitudes toward exercise from the beginning to the end of the 13-week exercise program (β = .24, p < .05). Main study results have revealed that in situ experiences predicted changes in affective attitude during multi-week exercise programs. These relevant in situ experiences encompass cognitive factors, the sensation of interoceptive cues, and affective responses to exercise. Considering the predictive role of affective attitudes for exercise behavior, these findings suggest that exercise interventions should put greater emphasis on specific exercise experiences.